Exercise priming with transcranial direct current stimulation: a study protocol for a randomized, parallel-design, sham-controlled trial in mild cognitive impairment and Alzheimer’s disease - Celina S. Liu (BMC, 2021)
Abstract Background Transcranial direct current stimulation (tDCS) is a non-invasive type of brain stimulation that uses electrical currents to modulate neuronal activity. A small number of studies have investigated the effects of tDCS on cognition in patients with Mild Cognitive Impairment (MCI) and Alzheimer’s disease (AD), and have demonstrated variable effects. Emerging evidence suggests that tDCS is most effective when applied to active brain circuits. Aerobic exercise is known to increase cortical excitability and improve brain network connectivity. Exercise may therefore be an effective, yet previously unexplored primer for tDCS to improve cognition in MCI and mild AD. Methods Participants with MCI or AD will be randomized to receive 10 sessions over 2 weeks of either exercise primed tDCS, exercise primed sham tDCS, or tDCS alone in a blinded, parallel-design trial. Those randomized to an exercise intervention will receive individualized 30-min aerobic exercise prescriptions to achieve a moderate-intensity dosage, equivalent to the ventilatory anaerobic threshold determined by cardiopulmonary assessment, to sufficiently increase cortical excitability. The tDCS protocol consists of 20 min sessions at 2 mA, 5 times per week for 2 weeks applied through 35 cm2 bitemporal electrodes. Our primary aim is to assess the efficacy of exercise primed tDCS for improving global cognition using the Montreal Cognitive Assessment (MoCA). Our secondary aims are to evaluate the efficacy of exercise primed tDCS for improving specific cognitive domains using various cognitive tests (n-back, Word Recall and Word Recognition Tasks from the Alzheimer’s Disease Assessment Scale-Cognitive subscale) and neuropsychiatric symptoms (Neuropsychiatric Inventory). We will also explore whether exercise primed tDCS is associated with an increase in markers of neurogenesis, oxidative stress and angiogenesis, and if changes in these markers are correlated with cognitive improvement. Discussion We describe a novel clinical trial to investigate the effects of exercise priming before tDCS in patients with MCI or mild AD. This proof-of-concept study may identify a previously unexplored, non-invasive, non-pharmacological combination intervention that improves cognitive symptoms in patients. Findings from this study may also identify potential mechanistic actions of tDCS in MCI and mild AD. Trial registration Clinicaltrials.gov, NCT03670615 . Registered on September 13, 2018.